2020
DOI: 10.1039/c9ra10204c
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil loaded pectin/chitosan nanoparticles preparation and optimization via Box–Behnken design against MCF-7 breast cancer cell lines

Abstract: Pec/CS/JO formulated nanocomposite showed a 13-fold increase in potency against cancer cells, whereas cell viability of normal cells wasn't affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 25 publications
1
23
1
Order By: Relevance
“…However, essential oils generally have low stability, high volatility, and a high risk of deterioration by exposure to direct heat, humidity, light, or oxygen [478]. Nanoformulations are a recent strategy being developed for essential oils and their constituents to solve these problems [463,[479][480][481][482].…”
Section: Essential Oilsmentioning
confidence: 99%
“…However, essential oils generally have low stability, high volatility, and a high risk of deterioration by exposure to direct heat, humidity, light, or oxygen [478]. Nanoformulations are a recent strategy being developed for essential oils and their constituents to solve these problems [463,[479][480][481][482].…”
Section: Essential Oilsmentioning
confidence: 99%
“… 81 The outcome was that pec/CS/JO NPs was effective against (MSF-7) breast cancer cells, which was evaluated by using MTT assay, where it was found that normal cells were not affected by the prepared nanoparticle. 81 Guo et al formulated a chitosan-based nanogel to inhibit the proliferation of breast cancer cell lines, where the model drug of 10-hydroxycamptothecin (HCPT) was entrapped into core by facile diffusion to form chitosan/10-hydroxycamptothecin (CS/HCPT). 82 From the prepared formulation the outcome was evaluated by assessing particle size, drug loading content and drug loading efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Attallah et al prepared pectin/chitosan/jasmine oil nanoparticles (Pec/ CS/JO NPs) by using Box-Behnken design (BBD). 81 The outcome was that pec/CS/JO NPs was effective against (MSF-7) breast cancer cells, which was evaluated by using MTT assay, where it was found that normal cells were not affected by the prepared nanoparticle. 81 Guo et al formulated a chitosan-based nanogel to inhibit the proliferation of breast cancer cell lines, where the model drug of 10hydroxycamptothecin (HCPT) was entrapped into core by facile diffusion to form chitosan/10-hydroxycamptothecin (CS/HCPT).…”
Section: Chitosan-based Pec Nanoparticles Outcomementioning
confidence: 99%
“…Encapsulation of EO has also been applied in fabrication of anticancer delivery systems. For instance, jasmine EO encapsulated into pectin/chitosan composite nanoparticles has been shown to exhibit anticancer activity approximately 13 times higher than the nonencapsulated EO and enhanced normal cell viability [91].…”
Section: Pharmaceutical Sectormentioning
confidence: 99%